2020
DOI: 10.1177/0885328220914408
|View full text |Cite
|
Sign up to set email alerts
|

A novel device to capture circulating tumor cells: Quantification and molecular analysis in lung cancer patients

Abstract: Here, we describe a novel microfilter device to capture circulating tumor cells in an efficient and low-cost manner. Then, we validated the safety and clinical utility of the novel microfilter device. We next performed mutation analysis from circulating tumor cells collected from lung cancer patients using this new device. Our results indicate that this microfilter system can be used to investigate the genome landscape of circulating tumor cells collected from lung cancer patients. Further, our results highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The herringbone microfluidic chip has been optimized by theoretical study such as COMSOL physics simulation in some other research and mainly applied in circulating cancer cells capture. [42][43][44][45][46] With sEVs emerging as biomarker in liquid biopsy, the herringbone microfluidic chip gradually applied for sub-group sEV capture. [43,47,48] And in this work, we mainly focus on new functionalization on interface of the chip and special application in pan-cancer screening.…”
Section: Fabrication Of the Hb Ev-chip And Strategy For Ps + Sev Isol...mentioning
confidence: 99%
“…The herringbone microfluidic chip has been optimized by theoretical study such as COMSOL physics simulation in some other research and mainly applied in circulating cancer cells capture. [42][43][44][45][46] With sEVs emerging as biomarker in liquid biopsy, the herringbone microfluidic chip gradually applied for sub-group sEV capture. [43,47,48] And in this work, we mainly focus on new functionalization on interface of the chip and special application in pan-cancer screening.…”
Section: Fabrication Of the Hb Ev-chip And Strategy For Ps + Sev Isol...mentioning
confidence: 99%
“…In literature, different system designed for CTCs analysis have been described with different costs and many advantages compared to tissue biopsy. A new micro-filter system to detect the CTCs with low costs was described by Cheng et al [ 12 ], whereas Maheswaran et al [ 13 ] demonstrated the ability to identify epidermal growth factor receptor mutations from CTCs isolated with a microchip device [ 14 ]. Actually, a recent study conducted at the MD Anderson Cancer Center (Houston, Texas), concluded that the NGS analysis on the tumor genome obtained from LB can completely replace tissue biopsy with the advantage of a reduced turnaround time (TAT).…”
Section: Diagnostic and Prognostic Value Of Circulating Biomarkersmentioning
confidence: 99%